A STUDY OF SMARTPHONE COMPANIES: DO INNOVATION CULTURE AND RADICAL INNOVATION AFFECT INSTITUTIONALIZATION AND SUSTAINABLE COMPETITION POSITIVELY? - Adiguzel, Zafer; Sönmez Çakır, Fatma; Kalyar, Masood Nawaz; Çakır, Fatma Sönmez (Univ Nove De Julho-Uninove, 2022)
Objective of the study: The present study examines how innovation culture and radical innovation elicit sustainable competition. The study proposes institutionalization as an important underlying mechanism that originates from innovation culture and radical innovation and provides the basis for sustainable competition. Design/methodology/approach: The data were collected from 763 employees working in smartphone companies located in Istanbul, Turkey. The analysis was performed employing PROCESS macro in order to test the hypothesized relationships. Findings: Results show that both innovation culture and radical innovation have a positive impact on institutionalization and sustainable competition. Moreover, the data also support the mediation effect of institutionalization in predicting sustainable competition. Practical implications: The findings imply that the structure of the firms must be ready for change in order to reap the benefits of sustainable competition. In fact, the creation of an innovation culture is very important in technology-intensive firms because there is a need to create common values that encourage employees to adopt innovative behaviors for sustainable competition. Furthermore, radical innovation can be more advantageous for firm-outcomes when large structural differences are identified and bridged successfully. Originality/value: The study develops a novel framework of innovation-competition using a structural perspective, empirically testing the proposed relationships using data from the technology-intensive industry of Turkey.
Keywords: Innovation Culture; Radical Innovation; Institutionalization; Sustainable Competition